WARTOŚCI ŻYCIA RODZINNEGO W ŚWIADOMOŚCI MATURZYSTÓW LUBELSKICH - Rola, Marcin (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article provides a sociological analysis of the empirical material concerning family values present in the consciousness of young Poles. The data were collected from Lublin high school graduates. The family is the primary place where the process of socialization and upbringing takes place, and where values, norms and patterns of behaviour are transmitted. Despite the crises and cultural transformations it experiences, the family remains the basic structure of social life and provides the environment for an individual to grow and become part of society and culture. For social researchers, it is important to diagnose the moral condition of today’s families in order to accurately determine the direction of changes that take place in modern societies. In this context, it is also important to examine young people’s moral consciousness of family values. As the young generation of Poles is a sensitive “barometer” of social changes, the study on their attitudes makes it possible to determine to what extent moral values are still transmitted in the family and to what extent they have changed or disappeared. Furthermore, it is the young people that in the near future will face the challenge of starting their own families and taking care of them, so it seems crucial to explore the problem in question within this social group.